How it all began - Lively, Penelope, 1933- (Penguin Books, 2012)
The mugging of a retired schoolteacher on a London street has unexpected repercussions for her friends and neighbors when it inadvertently reveals an illicit love affair, leads to a business partnership, and helps an immigrant to reinvent his life.